2023
DOI: 10.3892/ijmm.2023.5248
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the study of regulators of ferroptosis in head and neck squamous cell carcinoma (Review)

Abstract: Head and neck squamous cell carcinoma (HNScc), a common malignancy of the head and neck, is associated with a rapid progression, a high mortality rate and unsatisfactory curative effects. The treatment efficacy is unsatisfactory due to chemotherapeutic drug resistance, the lack of ideal therapeutic agents, as well as the absence of clinical prognostic models. Thus, the identification of novel potential therapeutic targets for its diagnosis and treatment is vital. Ferroptosis is an iron-dependent regulatory cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 127 publications
0
2
0
Order By: Relevance
“…Many anticancer drugs (Dabrafenib, vemurafenib,Val-boroPro) show a profound effect on programmed cell death, implied that programmed cell death,such as apoptosis,autophagy,ferroptosis,may play a role in cancer therapy [ 30 ]. Previous studies have shown that we can reduce cisplatin resistance in cancer cells, and enhance the sensitivity of tumor cells to chemotherapeutic drugs by promoting ferroptosis in tumor cells [ 31 ]. With the development of anticancer therapies that selectively induce cancer cell death, cuproptosis may become a new target for the treatment of HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Many anticancer drugs (Dabrafenib, vemurafenib,Val-boroPro) show a profound effect on programmed cell death, implied that programmed cell death,such as apoptosis,autophagy,ferroptosis,may play a role in cancer therapy [ 30 ]. Previous studies have shown that we can reduce cisplatin resistance in cancer cells, and enhance the sensitivity of tumor cells to chemotherapeutic drugs by promoting ferroptosis in tumor cells [ 31 ]. With the development of anticancer therapies that selectively induce cancer cell death, cuproptosis may become a new target for the treatment of HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…6a, Supplementary Table 11). For example, expression of CCL5, a proinflammatory chemokine for NK and other immune cells, was higher in MHRs, whereas expression of Ferritin Heavy Chain 1 (FTH1), associated with Treg recruitment and poor OS in HNSCC 42 , was higher in nMHRs. Gene set enrichment analysis (GSEA) revealed that several hallmark immune response pathways (e.g., interferon alpha and gamma response) were enriched in MHRs relative to nMHRs at baseline (Extended Data Fig.…”
Section: Baseline Cd8 + T Cells Have Higher Cytotoxicity and Frequenc...mentioning
confidence: 99%